Effect of plant-derived organic amendments on Meloidogyne incognita infecting okra, Abelmoschus esculentus L. (27th May 2020) - Premachandra, W. T. S. Dammini; Damithri, W. H. D. P. I.; Neilson, Roy
Abstract: Pot trials were conducted to determine the efficacy of incorporating fresh leaves of Morinda citrifolia, Lantana camara and Palm pressed fiber into soil, to manage Meloidogyne incognita, infecting okra, Abelmoschus esculentus L. All the amendments were effective against M. incognita with significantly reduced gall formation and multiplication, the greatest effect recorded was associated with plants amended with M. citrifolia . A reduction in number of galls and percentage galled-roots and, a reduction number of egg masses and females per root system highlighted an inhibition of gall formation and suppression of nematode multiplication, respectively, compared to the un-amended control. Tested amendments also improved the growth of okra plants with shoot weight exhibiting the greatest increase. Similar to root infection, M. citrifolia was associated with the greatest growth improvement of okra.